UPAYA PENINGKATAN PELAYANAN KARTU TANDA PENDUDUK MELALUI REFORMASI PELAYANAN PUBLIK - Mashoed, Mashoed (Jurnal Review Politik, 2013)
The research aims to identify the improvement of public services in the field of management of ID cards in the District of Pakal. The fundamental research questions are how does public services reformation in providing services to the society and what are the supporting and inhibiting factors, as well as strategy of improvement quality service in Pakal of Surabaya? This study suggests that the reform of bureaucracy and the quality of public services was good. It will be support the implementation of bureaucratic reform in order to improve the quality of public services, the change accordant to vision and mission, the application of one-day service even within 30 minutes, evening service and how to improve the profesialisme of apparatus by providing education and training.